The Ratio of a Urinary Tobacco-Specific Lung Carcinogen Metabolite to Cotinine is Significantly Higher in Passive than in Active Smokers - Vogel, Rachel Isaksson (2011)
4-(Methylnitrosamino)-1-(3-pyridyl)-1-butanol plus its glucuronides (total NNAL), metabolites of the lung carcinogen NNK, and total cotinine, metabolites of nicotine, are biomarkers of active and passive cigarette smoking. We calculated the total NNAL: total cotinine (× 10(3)) ratio in 408 passive (infants, children, adults) and 1088 active smokers. The weighted averages were 0.73 (95% CI 0.71, 0.76) for passive smokers and 0.07 (0.06, 0.08) for active smokers (p<0.0001). These results demonstrate that cotinine measurements may underestimate exposure of passive smokers to the lung carcinogen NNK in secondhand cigarette smoke. The total NNAL:total cotinine (× 10(3)) ratio may provide an improved biomarker for evaluating the health effects of passive smoking.